Development of Barbier-Grignard-type alkylation reaction using unactivated alkyl halides in water. - Shen, Zhi Liang. (2008)
The Barbier-Grignard-type alkylation reaction is one of the most important carbon-carbon bond formation reactions in organic synthesis. Classical methods developed for the Barbier-Grignard-type alkylation reaction are mainly limited to the use of moisture sensitive organometallic reagents such as Grignard reagent (RMgX). Therefore, the development of Barbier-Grignard-type alkylation reaction with the suppression of side reactions arose from the use of Grignard reagent in water are highly desirable. This thesis provides our premilinary studies towards the development of Barbier-Grignard-type alkylation reaction that can work in water.